Regulation and testing of wattmeters - Fielding Jr., George T (My University, 1903)
Introduction: The business of electric lighting and power distribution from central stations has grown to such a volume that millions of dollars change hands yearly in the transaction of that business. The commodity exchanged is the electric current and yet there is great uncertainty as to what that so called current really is. Considering this fact, the enormity of the business built upon this invisible something is rather surprising. The general lack of definite knowledge on the subject and the fact that the commodity is intangible are perhaps responsible for the laxity that has existed in the buying and selling of electrical power until a comparatively recent time. The sale of current involving large sums is often based upon measurements taken with poor, inefficient instruments or upon a system of calculation closely allied with guessing. Such .a manner of doing business would have resulted in bankruptcy in any other line, but the spirit of the age has entered the trade and the cry for the past few years has been for a more accurate system and this means better instruments. While the station manager knows that his financial success depends largely upon the excellence and efficiency of his plant yet he cannot shut his eyes to the fact that his income depends largely upon the system by which he sells his current. Dissatisfied Or suspicious customers are not conducive to prosperous trade, and dissatisfied they will be if they feel that there is inaccuracy or guessing in their accounts. The effect of poor measuring devices usually reacts in two ways upon the central station manager for beside trouble with customers he also has to stand a loss from inefficient metering, this loss often amounting to eight per cent of the current going through the meters. With the rapid strides of electrical enterprise, however, the improvement and manufacture of electric meters has in a large measure kept pace and today there are on the market a number of very efficient meters.
Citation: Fielding Jr., George T. Regulation and testing of wattmeters. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Principles of transformers; Alternating Currents; Power Transmission; Theses